Irradiation Haematopoiesis Recovery Orchestrated by IL-12/IL-12Rβ1/TYK2/STAT3-Initiated Osteogenic Differentiation of Mouse Bone Marrow-Derived Mesenchymal Stem Cells - Li, Fengjie; Zhang, Rong; Hu, Changpeng; Ran, Qian; Xiang, Yang; Xiang, Lixin; Chen, Li; Yang, Yang; Li, Shengwen Calvin; Zhang, Gang; Li, Zhongjun (Frontiers in Cell and Developmental Biology, 2021)
Repairing the irradiation-induced osteogenic differentiation injury of bone marrow mesenchymal stem cells (BM-MSCs) is beneficial to recovering haematopoiesis injury in radiotherapy; however, its mechanism is elusive. Our study aimed to help meet the needs of understanding the effects of radiotherapy on BM-MSC osteogenic potential. Here we found considerable effects of early use of IL-12 on the enhancement of osteogenic differentiation of BM-MSCs, the promotions of osteogenesis of the femur, and the recovery of bone marrow haematopoiesis of femur capacity of Balb/c mice. We also found the expression of IL-12 receptor beta 1 (IL-12Rβ1) of irradiated BM-MSCs was upregulated rapidly, which showed coincidental consistency with early use of IL-12 induced osteogenic differentiation enhancement. Furthermore, IL-12Rβ1 and tyrosine kinase 2 gene (Tyk2) silencing experiments and phosphotyrosine of signal transducer and activator of transcription 3 (p-STAT3) suppression experiments indicated the IL-12Rβ1/TYK2/STAT3 signaling is essential in IL-12-induced osteogenic differentiation enhancement of BM-MSCs. These findings suggested that IL-12 may exert BM-MSCs-based hematopoietic recovery function by repairing osteogenic differentiation abilities damages through IL-12Rβ1/TYK2/STAT3 signaling pathway after irradiation.